A Study of Quality Monitoring Equipments and Software Facilities available in Small and Medium scale Sheet-Fed Offset Printing Presses - Bijender, Pankaj Kumar, Seema Rani, Ankit Boora (International Journal of Advanced Science and Technology, 2020)
Standardization of all most all Printing operations and their demand from buyers has pushed printers at different labels to stay ahead in competition. Human vision has its own limitations and modern multicolour printing has reached at almost perfection label. To keep pace with high speed printing with international standard printers are relaying on machine vision at place of human eye. State of art testing and quality instruments are key success along with modern edge software being used for checking deviations and control of quality.